Characterization and virulence of Streptococcus agalactiae deficient in SaeRS of the two-component system - Li, Shiyu; Li, Wei; Liang, Qiancai; Cao, Jizhen; Li, Han; Li, Zhicheng; Li, Anxing (Frontiers in Microbiology, 2023)
There are a variety of regulatory systems in bacteria, among which the two-component system (TCS) can sense external environmental changes and make a series of physiological and biochemical reactions, which is crucial for the life activities of bacteria. As a member of TCS, SaeRS is considered to be an important virulence factor in Staphylococcus aureus, but its function in tilapia (Oreochromis niloticus)-derived Streptococcus agalactiae remains unknown. To explore the role of SaeRS in regulating virulence in the two-component system (TCS) of S. agalactiae from tilapia, ΔSaeRS mutant strain and CΔSaeRS complementary strain were constructed by homologous recombination. The results showed that the abilities of growth and biofilm formation of ΔSaeRS strain were significantly decreased when cultured in a brain heart infusion (BHI) medium (P<0.01). Also, the survival rate of the ΔSaeRS strain in blood was decreased when compared with the wild strain S.agalactiae THN0901. Under the higher infection dose, the accumulative mortality of tilapia caused by the ΔSaeRS strain was significantly decreased (23.3%), of which THN0901 and CΔSaeRS strains were 73.3%. The results of competition experiments in tilapia showed that the invasion and colonization abilities of the ΔSaeRS strain were also dramatically lower than those of the wild strain (P<0.01). Compared with the THN0901, the mRNA expression levels of virulence factors (fbsB, sip, cylE, bca, etc.) in the ΔSaeRS strain were significantly down-regulated (P<0.01). SaeRS is an important regulator of S.agalactiae virulence. It plays an important role in promoting host colonization and achieving immune evasion during the infection of tilapia. The results provide a basis for the TCS and virulence mechanism of S. agalactiae in tilapia .